Establishment and characterization of a canine chondrosarcoma cell line: Mango - Meilin Wang; Xiao Wang; Lixin He; Hongbo Gao; Wenxuan Li; Huili Feng; Qingyuan Zhao; Wenwen Zhang; Chengzong Li; Bohan Zhang; Changwei Qiu (BMC, 2023)
Abstract In the global progress of bone tumor research, established stable and long-lasting transgenic chondrosarcoma (CSA) cell lines are rare, mainly of murine and human origin, while the establishment of canine CSA cell lines has yet to be reported. This study established a canine CSA cell line to facilitate the basic clinical study of canine CSA. Fifty five cases of canine osteolytic disease were collected, and more than 10 bone tumor samples from dogs with typical clinical signs were used for primary cell culture. A cell line with stable passaging for more than 100 generations and mouse tumorigenic ability was successfully cultured. According to the clinical characteristics of the dog and the histopathological results of the primary tumor, CSA was diagnosed, and the CSA cell line was designated Mango. Immunohistochemical (IHC) results showed that the immunoreactivity of bone gamma-carboxyglutamate protein (BGLAP), secreted protein acidic and rich in cysteine (SPARC), alkaline phosphatase (ALPL), vimentin (VIM) and S100 were positive. However, the immunoreactivity of pan-cytokeratin (PCK), chromogranin A (CGA), and platelet endothelial cell adhesion molecule-1 (CD31) was negative. Immunofluorescence (IF) results showed that the protein expressions in the Mango cell line were consistent with the IHC identification of the primary tumor. The Mango cell line's doubling time was 43.92 h, and the cell formation rate exceeded 20%. There were abnormal chromosome numbers, hetero staining with toluidine blue, and certain calcification abilities. It could be passaged stably and continuously without changing the cell morphology and characteristics. In vivo, the cells were successfully injected into the nude mice model with a tumorigenic rate of 100%. The immunophenotype of the xenograft tumor was consistent with that of the primary tumor. Therefore, we effectively established a canine CSA cell line. As a promising cell material, this cell line can be used to construct a tumor-bearing model conducive to the subsequent basic research of canine CSA. Moreover, because of its similarity to human CSA, the animal model of CSA is also indispensable for investigating human CSA.